2012
DOI: 10.1007/s10488-012-0437-5
|View full text |Cite
|
Sign up to set email alerts
|

Inter-Organizational Collaboration in the Implementation of Evidence-based Practices Among Public Agencies Serving Abused and Neglected Youth

Abstract: This study examined the role of inter-organizational collaboration in implementing new evidence-based practices for addressing problem behaviors in at-risk youth. Semi-structured interviews were conducted with 38 systems leaders of probation, mental health, and child welfare departments of 12 California counties participating in a large randomized controlled trial to scale-up the use of Multidimensional Treatment Foster Care. Three sets of collaboration characteristics were identified: (1) characteristics of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
61
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 92 publications
(76 citation statements)
references
References 37 publications
2
61
0
3
Order By: Relevance
“…A re-examination of the 22 studies and an additional 6 studies published since 2009 revealed that only 5 studies (Aarons & Palinkas, 2007; Bachman et al, 2009; Palinkas et al, 2011; Palinkas et al, 2012; Slade et al, 2003) made a specific reference to purposeful sampling. An additional three studies (Henke et al, 2008; Proctor et al, 2007; Swain et al, 2010) did not make explicit reference to purposeful sampling but did provide a rationale for sample selection.…”
Section: Purposeful Sampling In Implementation Researchmentioning
confidence: 99%
“…A re-examination of the 22 studies and an additional 6 studies published since 2009 revealed that only 5 studies (Aarons & Palinkas, 2007; Bachman et al, 2009; Palinkas et al, 2011; Palinkas et al, 2012; Slade et al, 2003) made a specific reference to purposeful sampling. An additional three studies (Henke et al, 2008; Proctor et al, 2007; Swain et al, 2010) did not make explicit reference to purposeful sampling but did provide a rationale for sample selection.…”
Section: Purposeful Sampling In Implementation Researchmentioning
confidence: 99%
“…For those interested in supporting the successful adoption, implementation, and sustainability of evidence-based programs, understanding which partnerships can be created and maintained will be critical (Brown et al, 2012; Palinkas et al, 2014; Valente, Fujimoto, Palmer, & Tanjasiri, 2010; Valente, Palinkas, Czaja, Chu, & Brown, 2015). To date, however, the literature on the use of network analysis to strengthen community partnerships is largely theoretical and consists of secondary analyses (Bevc, Retrum, & Varda, 2015; Granner & Sharpe, 2004; Manning et al, 2014; Mattessich & Rausch, 2014; Provan, Veazie, Staten, & Teufel-Shone, 2005; Retrum, Chapman, & Varda, 2013; Varda & Retrum, 2012; Varda, Shoup, & Miller, 2011).…”
Section: Public Health Implicationsmentioning
confidence: 99%
“…A complete list of MIF constructs, their definitions, and their hypothesized level of influence is provided in Table 1. 30,[33][34][35][36][37][38][39][40][41][42][43][44][45][46] Description of the MA-CORD and CA-CORD Interventions…”
Section: Initial Conceptualization Of the Multilevel Implementation Fmentioning
confidence: 99%
“…63 Document analysis of project-related materials, such as investigator and coalition meeting minutes, which will be collected on an ongoing basis. Whereas these materials will primarily be used to document intervention activities and implementation processes, coalition meeting minutes will also be used to track changes in coalition size, diversity, stability, and outcomes (e.g., community changes, planning products, media products, 24,33,34 Inner setting Structural, political, and cultural context within a given entity responsible for implementation, including previous experience/history, resource availability, and leadership support for the intervention 35 Characteristics of individuals involved Knowledge, skills, beliefs, and personal characteristics of individuals responsible for implementing intervention activities and of intervention end users (e.g., children and their families). [36][37][38][39] Characteristics of intervention end users play a particularly important role in implementation of public health and chronic care management interventions.…”
Section: Qualitative Proceduresmentioning
confidence: 99%